1981
DOI: 10.1192/bjp.138.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Physostigmine and Arecoline: Effects of Intravenous Infusions in Alzheimer Presenile Dementia

Abstract: Physostigmine (0.25 mg-1 mg), arecoline (2 and 4 mg) and saline were administered intravenously over 30 minutes in a randomized double blind design to 11 patients with a clinical diagnosis of Alzheimer presenile dementia. Significant improvement was seen on a picture recognition test with physostigmine 0.375 mg and arecholine 4 mg. A trend towards improvement was also seen with physostigmine 0.25 mg and 0.75 mg, and arecholine 2 mg. For the majority of the patients improvement was only slight but in two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(90 citation statements)
references
References 24 publications
3
86
0
1
Order By: Relevance
“…Early studies of the cholinesterase inhibitor physostigmine observed significant drug-induced improvement in humans in long-term memory of words (Davis et al, 1978), in picture recognition (Christie et al, 1981), and significant dose-dependant improvement in aged monkeys in recent visual memory (Bartus and Uehara, 1979). More recently, physostigmine administration has changed the level of arousal and selective attention to visual tasks in pattern-flash stimulus tests in human PET studies of elderly subjects (Mentis et al, 2001).…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…Early studies of the cholinesterase inhibitor physostigmine observed significant drug-induced improvement in humans in long-term memory of words (Davis et al, 1978), in picture recognition (Christie et al, 1981), and significant dose-dependant improvement in aged monkeys in recent visual memory (Bartus and Uehara, 1979). More recently, physostigmine administration has changed the level of arousal and selective attention to visual tasks in pattern-flash stimulus tests in human PET studies of elderly subjects (Mentis et al, 2001).…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…These include such natural agents as arecoline (Christie et al, 1981) and pilocarpine (Caine, 1980), and synthetic compounds such as RS-86 (Mouradian et al, 1988). Clinical trials with such agents have generally been disappointing, at least partly due to the side effects associated with muscarinic receptor stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of inhibitors of cholinesterase have been used in these treatments, including physostigmine (Christie et al, 1981) and tetrahydroaminoacridine (Summers et al, 1986) for treatment of Alzheimer's patients. Since in these diseases the therapeutic aim is to increase the action of acetylcholine it might be counterproductive to use an acetylcholinesterase inhibitor which also depresses acetylcholine action at the level of the nicotinic cholinoceptor, although the importance of nicotinic receptor activation in the central effects of acetylcholinesterase inhibitors is unclear.…”
Section: Differences In the Action Between The Cholinesterase Inhibitorsmentioning
confidence: 99%